Poročanje o mednarodnem razvojnem sodelovanju v slovenskih medijih - Bučar, Maja (Javnost (Ljubljana), 2011)
The allocation of funding for international development cooperation is, according to several international studies, significantly shaped by public opinion. An extensive body of recent research demonstrates relationship between the impact of mass media, public opinion and the size of development aid. According to the results of public opinion polls, international development cooperation enjoys high public support in Slovenia, yet at the same time, Slovenia is one of the few EU member states where this support has decreased since the country's membership in EU. The paper focuses on the analysis of international development cooperation reported in Slovenian mass media. We explore the processes of gatekeeping and agenda-setting in the mediato evaluate the impact of these processes on the representation of specific topics. Under-representation of international development cooperation in the media indicates that the media are not influenced by public opinion (polls).
Keywords: mednarodno sodelovanje; mednarodna pomoč; razvojne perspektive; razvojna pomoč; razvojni projekti; množični mediji; mass media; javno mnenje; vplivi